An exceptional influx and successful breeding of Pantala flavescens on the Island of Malta (Maltese Archipelago) (Odonata: Libellulidae) - GAUCI, Charles (Fragmenta entomologica, 2022)
Pantala flavescens (Fabricius 1798) appeared in unprecedented numbers in summer and autumn 2020 on the island of Malta. Several males were observed holding territory over largely bare, small bodies of water, mostly at Chadwick Lakes and Fiddien. Breeding activity was witnessed several times and 128 exuviae were found of which 124 were collected.